Pengaruh penetapan harga dan penjualan terhadap kuantitas produk pada saat pandemi covid 19 - Hertina, Dede; Hekmatyar , Robby (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Corona virus disease (COVID-19) is an infectious disease caused by the SARS-CoV2 virus. Most people who contract COVID-19 will experience mild to moderate symptoms, and will recover without special treatment. However, some people will experience serious illnesses such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS) which require medical assistance. The Covid-19 Pandemic disaster that occurred, resulted in rising prices for medical sales and pharmacies.This study aims to analyze the effect of pricing and product sales on selling prices at Talitha Pharmacy, Cianjur City. This research is a qualitative research. The data collection technique used is the interview method, unstructured observation and tracing. This research was conducted at Talitha Pharmacy, Cianjur City. The results of the study stated that Pricing and Sales factors during the Covid-19 Pandemic at Talitha Pharmacy, Cianjur City had a significant effect on sales.